En introduktion til Sergei Bulgakovs teologi - Mejrup, Kristian Mejrup (Dansk Teologisk Tidsskrift, 2010)
An overlooked chapter in a Danish theological context is the sophiology and theology of Sergei Bulgakov who developed a theology based on the humanity of God. The Russian sophiological tradition draws no clear line between theology and philosophy. It mingles German idealism with Greek patristics, and a view of God, Goodness, Truth and Beauty is defended in a world full of cracks, antinomies and fragments of the Truth. Sophiology offers a view of the world englobed in divinity. Creation is a creation ex nihilo but also out of a superabundance in the inner divinity of the Triune God. Sophiology does not understand itself to be a new doctrine, but an interpretation of the doctrine of the Incarnation and the Trinity. Following the line of thought in Sergei Bulgakov’s sophiology, the relation between identity and differenc is rendered clear as a relation between God and the world. This article will particularly investigate the Christological and Trinitarian aspects of Bulgakov’s sophiology.